From Skull to Identity: Cephalometric Parameters as Predictors of Stature, Sex, and Ethnicity in Pakistan - Qudsia Hassan; Marvi Masood Farooqui; Samiuddin Ahmed (Pakistan Journal of Medicine and Dentistry)
Background: Head anthropometric measurements are crucial for identifying unknown bodies, dismembered parts, and decomposed corpses, especially when DNA profiling is unavailable. These measurements help distinguish sex and ethnic differences, which are vital in forensic investigations. Understanding biophysical skeletal variations across ethnicities is vital for medico-legal identification. This study aimed to correlate and predict stature, sex, and ethnicity using head and face measurements in a Karachi-based population.